1991
DOI: 10.3109/00016359109041137
|View full text |Cite
|
Sign up to set email alerts
|

Initial caries diagnosis in rat molars, using laser fluorescence

Abstract: Scoring of enamel caries in rat molars in ordinary light and in laser fluorescence was compared. Fifty rats were infected with Streptococcus mutans; 5 served as control rats, and the other 45 were fed a cariogenic diet for 15-20 days. With Keyes's system, the total enamel caries score for 35 of the test rats was 29.1 lesions per rat (l/r) in ordinary light and 39.6 l/r in laser fluorescence. The corresponding scores for fissure caries were 15.9 l/r and 21.6 l/r, respectively. Fissure caries scores of thin, lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…5 Detection of proximal lesions is technically more difficult, and in this setting, argon laser-induced fluorescence offers a valuable adjunct to conventional methods. [6][7][8][9] The differential water content of early fissure caries and sound occlusal enamel has also led to the development of methods using the carbon dioxide laser to reveal such lesions, [10][11][12] and to modify the fissure system to increase resistance to future carious attack. 11 Two key advantages of laser-based systems are their high sensitivity, and the lack of attendant risks of ionizing radiation.…”
Section: 2mentioning
confidence: 99%
“…5 Detection of proximal lesions is technically more difficult, and in this setting, argon laser-induced fluorescence offers a valuable adjunct to conventional methods. [6][7][8][9] The differential water content of early fissure caries and sound occlusal enamel has also led to the development of methods using the carbon dioxide laser to reveal such lesions, [10][11][12] and to modify the fissure system to increase resistance to future carious attack. 11 Two key advantages of laser-based systems are their high sensitivity, and the lack of attendant risks of ionizing radiation.…”
Section: 2mentioning
confidence: 99%
“…Several investigators [Bjelkhagen et al, 1982;Sundström et al, 1985; AngmarMånsson and ten Bosch, 1987;Hafström-Björkman et al, 1991de Josselin de Jong et al, 1995;Emami et al, 1996;Angmar-Månsson et al, 1996] have demonstrated…”
mentioning
confidence: 99%
“…No entanto, muitos outros métodos estão sendo desenvolvidos para auxiliar no diagnóstico da cá-rie, como transluminação por fibra óptica, o exame endoscópico, utilização de elásticos separadores, uso de luz difusa, iluminação ultravioleta, penetração de corantes, penetração de iodo, resistência elétrica, ultra-som, radiografia digitalizada e xerorradiografia 13 . Na década de 90, algumas pesquisas têm demonstrado boa perspectiva relacionada a utilização do laser fluorescente como auxiliar no diagnóstico da cárie 1,3,4,7,8,15 , comprovando que o laser é capaz de detectar desmineralizações iniciais, principalmente quando é adicionado corante fluorescente na superfície dental que se quer avaliar 5,6 . Isto pode ser explicado, pois lesões de cárie (iniciais ou cavitadas) aparecem como áreas escuras quando excitadas pelo feixe de luz laser (488 nm).…”
Section: Introductionunclassified